1997
DOI: 10.1055/s-0038-1656057
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thrombopoietin Level Is Not Regulated by Transcription but by the Total Counts of both Megakaryocytes and Platelets during Thrombocytopenia and Thrombocytosis

Abstract: SummaryThrombopoietin (Tpo) regulates platelet production, but the mechanisms regulating the serum Tpo level and platelet count in circulation have been a subject of debate. Tpo was reported to be expressed mainly in liver and kidney, but we found that Tpo is expressed in all tissues examined: abundantly in liver, kidney, muscle, colon, brain and intestine, and moderately in bone marrow, spleen, lung, stomach, heart, thymus, ovary, and endothelial and leukemic cell lines. The levels of Tpo transcripts in major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 25 publications
4
67
1
1
Order By: Relevance
“…22,23 Plasma TPO levels are negatively regulated by platelets and megakaryocytes through their binding of TPO. 24,25 Some studies show an inverse correlation between TPO levels and BM megakaryocyte count, 26,27 but the TPO levels of patients with RAEB were consistently low in our study despite the low megakaryocyte content (data not shown). Low TPO levels in MDS patients with a poor prognosis may be Y. Seiki et al 904 haematologica | 2013; 98(6) Specificity Figure 2.…”
Section: Discussioncontrasting
confidence: 38%
“…22,23 Plasma TPO levels are negatively regulated by platelets and megakaryocytes through their binding of TPO. 24,25 Some studies show an inverse correlation between TPO levels and BM megakaryocyte count, 26,27 but the TPO levels of patients with RAEB were consistently low in our study despite the low megakaryocyte content (data not shown). Low TPO levels in MDS patients with a poor prognosis may be Y. Seiki et al 904 haematologica | 2013; 98(6) Specificity Figure 2.…”
Section: Discussioncontrasting
confidence: 38%
“…When platelets and megakaryocytes are decreased in number, less thrombopoietin is removed from plasma, and the thrombopoietin level rises, while when platelet numbers increase, more thrombopoietin is cleared from the plasma and the thrombopoietin level falls again. 2 In addition to the thrombopoietin (THPO) and c-Mpl (MPL) genes, a large number of genes encoding membrane glycoproteins, cytoskeletal components and proteins involved in transcription, cell cycle regulation and signaling have been demonstrated to participate in the differentiation of pluripotent stem cells to mature platelet-shedding megakaryocytes. 3 Defined as a platelet count less than 150¥10 9 /L, thrombocytopenia is usually an acquired disorder.…”
mentioning
confidence: 99%
“…Thrombocytopenia, a reduction in platelets, stimulates the production of thrombopoietin (TPO) and promotes megakaryocytopoiesis. 7 As platelet counts return to normal, TPO is effectively cleared from the circulation. This involves TPO binding to its receptor, c-mpl, and its uptake into platelets and Mk.…”
mentioning
confidence: 99%